2016
DOI: 10.1016/j.scitotenv.2016.03.181
|View full text |Cite
|
Sign up to set email alerts
|

Targeted metabolomics of Gammarus pulex following controlled exposures to selected pharmaceuticals in water

Abstract: The effects of pharmaceuticals and personal care products (PPCPs) on aquatic organisms represent a significant current concern. Herein, a targeted metabolomics approach using liquid chromatography-high resolution mass spectrometry (LC-HRMS) is presented to characterise concentration changes in 29 selected metabolites following exposures of aquatic invertebrates, Gammarus pulex, to pharmaceuticals. Method performance revealed excellent linearity (R2 > 0.99), precision (0.1–19%) and lower instrumental limits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…In addition to screening for small micro-contaminant molecules, screening of biota for thousands of endogenous metabolites can be achieved simultaneously (i.e. metabolomics) ( Gómez-Canela et al., 2016 ; Toyota et al., 2016a ; Viant and Sommer, 2013 ). Environmental metabolomics-based studies have focused on the effect of biotic and abiotic stressors on both terrestrial and aquatic organisms and several have used nuclear magnetic resonance spectroscopy (NMR) and/or GC/LC-MS ( Broeckling et al., 2005 ; Bundy et al., 2004 ; Bussell et al., 2008 ; Griffin et al., 2000 ; Hines et al., 2007 ; Skelton et al., 2014 ).…”
Section: Characterising the Exposome With Chromatography And High Resmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to screening for small micro-contaminant molecules, screening of biota for thousands of endogenous metabolites can be achieved simultaneously (i.e. metabolomics) ( Gómez-Canela et al., 2016 ; Toyota et al., 2016a ; Viant and Sommer, 2013 ). Environmental metabolomics-based studies have focused on the effect of biotic and abiotic stressors on both terrestrial and aquatic organisms and several have used nuclear magnetic resonance spectroscopy (NMR) and/or GC/LC-MS ( Broeckling et al., 2005 ; Bundy et al., 2004 ; Bussell et al., 2008 ; Griffin et al., 2000 ; Hines et al., 2007 ; Skelton et al., 2014 ).…”
Section: Characterising the Exposome With Chromatography And High Resmentioning
confidence: 99%
“…Furthermore, glucocorticoid and lipid metabolism was disrupted and a 470-fold decrease in palmitoyl carnitine concentrations were observed (used in fatty acid transport). We also recently studied sub-lethal concentration exposures of three pharmaceutical compounds (propranolol, triclosan and nimesulide) to G. pulex ( Gómez-Canela et al., 2016 ). Metabolic changes in a range of amino acids and other metabolites were identified and quantified using SIL-IS.…”
Section: Characterising the Exposome With Chromatography And High Resmentioning
confidence: 99%
“…The only non-lipid related metabolite feature we identified with a level 1 certainty was phenylalanine, which has also been reported in a previous metabolomics study on PPL exposure. 46 The direct inhibition of tyrosine hydroxylase (TH) by PPL is a likely explanation for the relative increase of phenylalanine in the two highest exposure concentrations in our data (Fig. 5b).…”
Section: Ppl Mode Of Actionmentioning
confidence: 72%
“…Due to advantages that have been discussed elsewhere (Bundy et al, 2009;Lankadurai et al, 2013), metabolomics has been shown to be a particularly useful "-omics" approach for evaluating comprehensive biological responses to various environmental stressors. For example, this approach has been extensively employed to investigate the MOAs of various xenobiotics, including nanoparticles (Ratnasekhar et al, 2015), PPCPs (Gomez-Canela et al, 2016), and EDCs (Davis et al, 2017), through laboratory-based animal (e.g., rodents, fish, and invertebrates) exposures. In addition, field-based metabolomics assessments using on-site exposure of fish have been used successfully to investigate the biological effect of complex contaminant mixtures discharging from both point (e.g., WWTP effluent) and nonpoint sources (Davis et al, 2013;Skelton et al, 2014).…”
Section: Introductionmentioning
confidence: 99%